2021
DOI: 10.25034/ijcua.2022.v6n1-2
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of Tourism Development in the city of Ain-Sukhna, Egypt

Abstract: Tourism is a major economic source for Egypt, due to its significant natural and cultural attractions. Yet, rapid development and construction of touristic facilities have a negative impact on the fragile natural and cultural heritage. This paper studies the recent touristic developments of the coastal stretch of Ain-Sukhna on the Red Sea coastal region of Galala Mountain, and their impact on the surrounding natural and cultural attractions. Coral reefs and rich marine life have made this stretch among the pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…surrounding ecosystem is protected with minimal changes due to the use of indigenous and semiindigenous plants, trees, and ground cover palettes, as well as recycled water and an effective water conservation irrigation system. [14] The city's architectural design character is consistent with the distinctive coastal mountain nature. The building materials will be from the Red Sea area quarries and landscape planting will be true to sustainable environment.…”
Section: El Galala Plateaumentioning
confidence: 72%
“…surrounding ecosystem is protected with minimal changes due to the use of indigenous and semiindigenous plants, trees, and ground cover palettes, as well as recycled water and an effective water conservation irrigation system. [14] The city's architectural design character is consistent with the distinctive coastal mountain nature. The building materials will be from the Red Sea area quarries and landscape planting will be true to sustainable environment.…”
Section: El Galala Plateaumentioning
confidence: 72%
“…(Tallet 2012) Sukhna was famous as the best place for camping and one-day school trips until recent developments took place that occupied most of the virgin and public beaches. Mahgoub studied the recent touristic developments of the coastal stretch of Ain-Sukhna on the Red Sea coastal region of Galala Mountain, and their impact on the surrounding natural and cultural attractions (Mahgoub 2022). He indicated that since the 1967 War the region was designated a military restricted zone and was off-limits to civilian and public activities.…”
Section: International Journal Of Multidisciplinary Studies In Archit...mentioning
confidence: 99%
“…The success of Porto Sukhna encouraged more luxurious developments and gated communities to be established in the area like La Vista and Telal. (Mahgoub 2022) Recently, development has started on the Galala Mountain Plateau following the construction of Galala Mountain Road and te establishment of Galala City, located 700 meters above sea level on the Galala al-Bahariya Mountains between Ain-Sukhna and Zaafarana, covering approximately 19,000 feddans. The city hosts Galala University that started operational on 2020 with 1500 students, and currently 5000 students, in 16 fields of studies and 37 programs, and is planned to grow to 25,000 students by 2030.…”
Section: Climate and Environment Changesmentioning
confidence: 99%
See 1 more Smart Citation